Ethics, Diseases and Communities - Haque, Anwar Ul (International Journal of Pathology, 2018)
What does ethics have to do with diseases? And whodetermines what ethics is? These are two importantfundamental questions which come to mind when weponder upon a particular behavior as ethical or unethical!The issue is further confused when question oflegal versus ethical is raised. Are legal actions necessarilyethical and illegal actions unethical? Is theresame uniform criteria to determine “legal” across theglobe. An illegal action in one country may be quitelegal in another country.